Prevalencia de las enfermedades en los adultos mayores que acuden al Centro Gerontológico Sagrada Familia, Cotopaxi 2015 - Madrid Lalvay, Mayra Elizabeth (2015)
Shared by all specialists in gerontology aim to provide quality care to elderly people , provide care where professionals from different care levels. The consequences of this practice are manifested in different levels , personally and professionally speaking, but it will be the impact on the health physics geronto which leads to an analysis of this interaction. The research was conducted strictly sustained in the review of documents or information about the variables that were investigated, in order to expand concepts and research-related criteria, so it is imminently considered a documentary or bibliographic research. On the other hand Descriptive Research, field and Social, thus it could spell were also used, an analytical, critical study and know the vulnerability of the elderly in their ability to perform daily activities, Gerontology Center “Sagrada Familia” del Canton La Mana. Once the data is collected and processed statistically by the method of simple count for descriptive analysis, expressed in absolute numbers, calculating percentages and brought to tables for better understanding and interpretation. The type of sample used is probabilistic, and within this type of sampling intentional accidental sampling was chosen so that the selection of the research sample was constituted by 20 seniors who attended Gerontology Center "Sagrada Familia" Canton's Maná. during the implementation of the survey. KEYWORDS: PREVALENCE, DISEASE, ELDERLY, GERONTOLOGY CENTER, ELDERLY CARE.